The long-term effects of military conscription on educational attainment and wages - Frank Hubers; Dinand Webbink (IZA Journal of Labor Economics, 2015)
This study investigates the long-term effects of peace-time military conscription on educational attainment and earnings by exploiting a policy change that exempted a complete birth cohort from military service. We find that compulsory military service decreases the proportion of Dutch university graduates by 1.5 percentage points from a baseline of 12.3 per cent. In addition, being a conscript reduces the probability of obtaining a university degree by almost four percentage points. The effect of military service on earnings is also negative and long-lasting. Approximately 18 years after military service, we still find a negative effect of 3 to 4 per cent. The effect of conscription on educational attainment does not fully explain the wage reduction.
Keywords: H56; J31; J24; 330; Military conscription; Long-term earnings; Human capital; University enrolment